2023
DOI: 10.1111/cag.12876
|View full text |Cite
|
Sign up to set email alerts
|

Un classement multicritère des villes du québec pour favoriser la prise en compte de leurs différences

Michel Rochefort,
Thi‐Thanh‐Hiên Pham,
Paul‐Émile Tchinda
et al.

Abstract: When it comes to making planning and development decisions, the concepts of small, medium‐sized, or large cities are sometimes used to adapt public policies and instruments, or even to highlight challenges that are specific to certain categories of city. In this article, we take a look at the various dimensions that can be used to characterize cities, so as to empirically test a multi‐criteria approach and build a typology of Quebec cities. Using an ascending hierarchical classification, we derive 11 classes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…De plus, les critères numériques ne tiennent généralement pas compte du fait qu'une ville de moindre envergure se distingue par des façons de faire particulières, par l'image qu'elle se fait d'elle‐même, par l'émotion qui s'en dégage, par le ressenti du lieu et les aspirations de ses habitants (Bell et Jayne, 2009, p. 690). De nombreux auteurs ont souligné qu'en se limitant à la taille, on escamote également le rôle de ces villes au sein de leur environnement régional (Carrier et Demazière, 2012; Hinderink et Titus, 2002; Proulx, 2006 Rochefort et al, 2023). Pourtant, les chercheurs retiennent invariablement la population totale pour différencier les PMV des grandes villes (Grant et al, 2019).…”
Section: Les Petites Et Moyennes Villes Canadiennes : Une Utilité Ren...unclassified
See 2 more Smart Citations
“…De plus, les critères numériques ne tiennent généralement pas compte du fait qu'une ville de moindre envergure se distingue par des façons de faire particulières, par l'image qu'elle se fait d'elle‐même, par l'émotion qui s'en dégage, par le ressenti du lieu et les aspirations de ses habitants (Bell et Jayne, 2009, p. 690). De nombreux auteurs ont souligné qu'en se limitant à la taille, on escamote également le rôle de ces villes au sein de leur environnement régional (Carrier et Demazière, 2012; Hinderink et Titus, 2002; Proulx, 2006 Rochefort et al, 2023). Pourtant, les chercheurs retiennent invariablement la population totale pour différencier les PMV des grandes villes (Grant et al, 2019).…”
Section: Les Petites Et Moyennes Villes Canadiennes : Une Utilité Ren...unclassified
“…Comme le développement de ces villes suit incontestablement des parcours différents, il ne serait pas réaliste de proposer une théorie unique ou des politiques pouvant s'appliquer à l'ensemble des PMV (Hinderink et Titus, 2002). Au cours de la préparation de ce recueil de textes, les auteurs et autrices ont néanmoins identifié·e·s sept critères pouvant servir à définir et caractériser une ville : la population, la densité, l'occupation du territoire, l'influence ou la zone d'influence (notamment, rôle de la ville dans sa structure et sa gouvernance), le type d'économie, le transport régional (par exemple, la mobilité de la main‐d'œuvre) et les défis socioéconomiques (Rochefort et al, 2023). En outre, nous avons demandé à l'équipe de rédaction de répondre aux questions théoriques et empiriques qui suivent : …”
Section: Les Petites Et Moyennes Villes Canadiennes : Une Utilité Ren...unclassified
See 1 more Smart Citation
“…Recognizing that these cities have different developmental trajectories, it is unrealistic to generate a single theory of universal policies for SMCs (Hinderink & Titus, 2002). In designing this section, however, the authors identified seven criteria that can be used to identify thresholds for defining and characterizing cities: population size, density, settlement pattern, area of influence (including the role of the city in its structure and governance), type of economy, regional commuting (mobility including for work), and socioeconomic challenges (Rochefort et al, 2023). We asked the authors to respond to the following theoretical and empirical questions: …”
Section: Spotlight On Canadian Small and Mid‐sized Cities—they Matter...mentioning
confidence: 99%
“…Numeric definitions also generally ignore how “smallness is bound up with particular ways of acting, self‐images, structures of feeling, senses of place, aspirations” (Bell & Jayne, 2009, p. 690). Focusing on size alone also ignores the role that these cities play in their region (Carrier & Demazière, 2012; Hinderink & Titus, 2002; Proulx, 2006; Rochefort et al, 2023), and yet researchers invariably consider population as a bellwether for differentiating SMCs from their large city counterparts (Grant et al, 2019). What does the term “SMC” do for us besides acting as a beacon for other researchers interested in similar themes?…”
Section: Spotlight On Canadian Small and Mid‐sized Cities—they Matter...mentioning
confidence: 99%